Bushen Huoxue Acupuncture Inhibits NLRP1 Inflammasome-Mediated Neuronal Pyroptosis in SAMP8 Mouse Model of Alzheimer’s Disease - Zhang T (Dove Medical Press, 2021)
Ting Zhang,1 Bin Guan,1 Sipin Tan,2 Hong Zhu,1 Dan Ren,1 Ruomeng Li,1 Lan Xiao1 1Department of Traditional Chinese Medicine, The Third Xiangya Hospital of Central South University, Changsha, Hunan, 410008, People’s Republic of China; 2Key Laboratory of Sepsis, Translational Medicine of Hunan, Department of Pathophysiology, Xiangya School of Medicine, Central South University, Changsha, Hunan, 410008, People’s Republic of ChinaCorrespondence: Lan XiaoDepartment of Traditional Chinese Medicine, The Third Xiangya Hospital of Central South University, 138 Tongzipo Road, Changsha, Hunan, 410008, People’s Republic of ChinaTel +86-15802686038Email xiaol038@163.comBackground: It was indicated that nucleotide-binding oligomerisation domain‑like receptor protein 1 (NLRP1) inﬂammasome-mediated pyroptosis is involveg in the progression of Alzheimer’s disease (AD). This study was designed to explore the effect of Bushen Huoxue Acupuncture on cognitive defect and NLRP1 inflammasome-mediated pyroptosis in AD mouse.Methods: Senescence-accelerated mouse prone 8 (SAMP8) mice were used as a model of AD. Bushen Huoxue Acupuncture was performed in four acupoints: “Baihui acupoint” (GV20), “Shenshu acupoint” (BL23), “Xuehai acupoint” (SP10), and “Geshu acupoint” (BL17). Morris water maze test was performed to evaluate the cognitive function of the mouse. The levels of Aβ1-40, Aβ1-42, IL-1β, and IL-18 were examined by ELISA assay. Neuronal apoptosis and damage in hippocampal tissues were measured using TUNEL and Nissl staining, respectively. The expression of NLRP1, ASC, cleaved caspase-1, IL-1β, and IL-18 was examined using Western blot.Results: Bushen Huoxue Acupuncture improved the learning and memory deficits of AD mouse. Meanwhile, Bushen Huoxue Acupuncture decreased the production of Aβ in hippocampal tissues of SAMP8 mice and attenuated the neuronal apoptosis and damage. Furthermore, Bushen Huoxue Acupuncture inhibited NLRP1 inﬂammasome activation in SAMP8 mice.Conclusion: Bushen Huoxue Acupuncture could notably attenuate the cognitive defect of mouse AD model and inhibit NLRP1 inflammasome-mediated pyroptosis.Keywords: Bushen Huoxue Acupuncture, Alzheimer’s disease, NLRP1 inflammasome, pyroptosis, hippocampal neurons